Respiratory Pathophysiology Simulation Cases (Pneumothorax and Pneumonia) - Jeremy B. Richards; Emily M. Hayden (Association of American Medical Colleges, 2012)
Abstract While preclinical medical students are generally adept at discussing the clinical consequences of pathophysiologic mechanisms in classroom settings, they often have difficulty applying pathophysiologic mechanisms to clinical problems in clinical settings. Simulation experiences offer a safe and controlled opportunity for students to experience clinical scenarios, and well-designed simulation scenarios and well-prepared faculty supervisors can help students apply pathophysiologic mechanisms to clinical problems in these settings. This curriculum provides the background, logistics, goals, objectives, and foundation for debriefing on two clinical scenarios involving respiratory pathophysiology. Pneumothorax and pneumonia are considered in two separate cases with an emphasis on clinical diagnosis, management, and relevant pathophysiology. The majority of student groups that participated in this resource were able to complete both cases with adequate time for debriefing. Students were generally able to diagnose and elect appropriate treatment for case 1 without significant delay or difficulty. Of note, these students had experienced a similar case of pneumothorax during the first week of their first year of medical school and may have had an easier time diagnosing the patient because of this.